A Statistical Multiplexing Method for Traffic Signal Timing Optimization in Smart Cities - Ben Ahmed Mohamed; Boudhir Anouar Abdelhakim; Bouhorma Mohammed; Ben Ahmed Kaoutar (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Urban road traffic is the heart of many problems: more recent years, this critical aspect involved every day is unfavorable to many fields, such as economics or ecology. For these reasons, the Intelligent Transportation Systems (ITS) have emerged to best optimize the expenditure of the user on often complex road networks. In this paper, after studying the backgrounds of such systems, we propose a system of control of traffic lights through the use of statistical multiplexing technique based on fixed and vehicular networks of wireless sensors. We will see that this architecture can be flexible within the framework of ITS and participate in low cost to obtain interesting results. The simulation results prove the efficiency of the traffic system in an urban area with an adaptable and dynamic traffic road, because the average waiting time of cars at the intersection is sharply dropped when the red light duration is 65 s and the green light time duration is 125 s. DOI: http://dx.doi.org/10.11591/telkomnika.v15i1.8092